PJMHS 2021
DOI: 10.53350/pjmhs2115123161
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Correlation of Depression in Melasma Patients

Abstract: Background: Melasma is hyper-pigmentation of skin, usually seen in young female adults, and previous studies have established substantial psychosocial burden associated with this disease. Aim: To measure the frequency of depression in melasma patients and its correlation with severity of melasma Study Design: Descriptive cross-sectional study. Place and duration of study: Dermatology OPD, HIT Hospital Taxila from 1st January 2021 to 31st August 2021 Methods: One hundred consecutive patients of melasma diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Among 16 studies, 10 studies were conducted in Asia, 4 in the Americas ( 19 , 22 , 26 , 29 ), and 2 in others [Europe ( 16 ) and Africa ( 27 )]. To assess depression, eight studies used the Hospital Anxiety and Depression Scale (HADS) ( 16 , 17 , 19 , 21 , 22 , 24 , 27 , 29 ), three used the Patient Health Questionnaire-9 (PHQ-9) ( 18 , 20 , 25 ), two used the Self-rating Depression Scale (SDS) ( 23 , 31 ), one used the Hamilton Depression Scale (HDRS) ( 28 ), one used the International Classification of Diseases-WHO 1992 (I.C.D-10) ( 30 ), and one was based on medical history (taking antidepressants) ( 26 ). Four studies reported the prevalence of depression in healthy controls ( 16 , 22 , 24 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 16 studies, 10 studies were conducted in Asia, 4 in the Americas ( 19 , 22 , 26 , 29 ), and 2 in others [Europe ( 16 ) and Africa ( 27 )]. To assess depression, eight studies used the Hospital Anxiety and Depression Scale (HADS) ( 16 , 17 , 19 , 21 , 22 , 24 , 27 , 29 ), three used the Patient Health Questionnaire-9 (PHQ-9) ( 18 , 20 , 25 ), two used the Self-rating Depression Scale (SDS) ( 23 , 31 ), one used the Hamilton Depression Scale (HDRS) ( 28 ), one used the International Classification of Diseases-WHO 1992 (I.C.D-10) ( 30 ), and one was based on medical history (taking antidepressants) ( 26 ). Four studies reported the prevalence of depression in healthy controls ( 16 , 22 , 24 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported the prevalence of depression in healthy controls ( 16 , 22 , 24 , 26 ). When evaluated by JBI quality assessment criteria, seven studies were rated as high quality ( 16 , 18 , 21–24 , 28 ), six were rated medium quality ( 19 , 20 , 25–27 , 31 ), and three were rated low quality ( 17 , 29 , 30 ). The details of the quality assessment for the 16 included studies are presented in the Supplementary Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Out of the total patients assessed, 18 did not show any signs of depression, while mild depression in 38 cases, followed by, moderate depression was in 31 cases, moderate to severe depression was in 6 cases and 7 had severe depression. 14 In the line of this series Jawaid K et al 3 conducted the study to investigate the incidence of depressive disorders and anxiety in the patients of melasma and they found anxiety in 19.49% of the patients and depression in 10.77% of the patients those having melasma. This frequency of anxiety and depression was lower compared to our findings, and this may because of difference in study sample size, selection criteria and severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the severity of depression and anxiety were statistically insignificant according to gender, marital status, duration of disease and types of skin disorder (p->0.05). In the comparison of this study Naheed A et al 14 use the Patient Health Questionnaire 9 (PHQ-9) to assess depression in patients with melasma. Out of the total patients assessed, 18 did not show any signs of depression, while mild depression in 38 cases, followed by, moderate depression was in 31 cases, moderate to severe depression was in 6 cases and 7 had severe depression.…”
Section: Discussionmentioning
confidence: 99%